A review of particulate pollution over Himalaya region: Characteristics and salient factors contributing ambient PM pollution. (1st February 2023) - Hassan, Muhammad Azher; Mehmood, Tariq; Liu, Junjie; Luo, Xiaosan; Li, Xinghua; Tanveer, Mohsin; Faheem, Muhammad; Shakoor, Awais; Dar, Afzal Ahmed; Abid, Muhammad
Abstract: The Himalayas, which include delicate and unspoiled ecosystems, have the third-largest glacier ice store in the world. Recent research reveals that anthropogenic and natural factors contribute to the deteriorating air quality in the region. Rising particulate matter (PM) levels might have devastating effects on the regional climate, hydrologic cycles, and ecology. Given the scarcity of studies (the majority of which are of short duration and focus on a single pollutant and satellite-based observation), unique topography, meteorological characteristics, monsoon dynamics, temperature inversion, and mixing of pollution emission from local and distant sources, it is difficult to understand the general pollution trend in the Himalaya. Nonetheless, past studies indicate that local biomass burning, long-distance transport, especially from the Indo-Gangetic Plain (IGPs), dust storms, and tourist activities are the primary drivers to rising PM pollution in the Himalayas region. Emissions from these sources develop exponentially and encompass severe pollution episodes because of the IGP's complicated hilly terrain, cloud condensation nucleation process, atmospheric brown clouds (haze), dust storm, and transport of PM from crop residue burning (especially during the post-monsoon season). In light of this, the current work outlines the sources, factors, and variables that contribute to the Himalayan region's rising pollution levels and sheds light on significant areas of recent research. The present study examines in depth the consequences of the monsoon, the dynamics of pollution in IGP, and the movement of PM from IGP to the Himalayan region. This review aims to highlight research gaps and limitations in the existing literature for a better understanding of the current PM pollution in the Himalayas and surrounding sites, which is essential for understanding climate change and health consequences in this region, and to provide significant theoretical and practical implications for assessing particulate pollution in the Himalayas region. Highlights: Characteristics of PM pollution in the Himalayas region are discussed. As a distant source, CRB in IGP contributes substantially to PM pollution in the Himalayas. PM pollution at high-altitude locations in the Himalayas is increasing. The unique topography and local weather dynamics intensify pollution in the Himalayas. Increasing black carbon in the Himalayas jeopardizes the monsoon and hydrological cycle.